2014
DOI: 10.5433/1679-0359.2014v35n1p193
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade espacial de atributos físico-químicos de um Latossolo Vermelho-Amarelo distrófico em sistema plantio direto

Abstract: ResumoO conhecimento da variabilidade espacial dos atributos químicos e físicos no solo é muito importante, principalmente, para a agricultura de precisão. A geoestatística vem em busca de aprimorar técnicas que possam viabilizar o uso correto e responsável do solo. Assim, durante o ano agrícola 2011/2012, em área de plantio de direto com a cultura do milho, no município de Gurupi (TO), no Cerrado brasileiro, objetivou-se analisar a variabilidade espacial de atributos físico-químicos de um Latossolo VermelhoAm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
0
8
0
5
Order By: Relevance
“…The spatial dependency index (SDI) corresponded to a strong spatial dependency only for the Cu attribute, classifying it as a moderate spatial dependency for the yield, C, pH, Mg, and K data. The attributes Fe, Mn, and Ca presented weak spatial dependency (Table 2), corroborating the results of Mondo et al (2012) andNegreiros Neto et al (2014). The data were interpolated by the ISD, ID, and ordinary kriging methods, and thematic maps were constructed (Figure 2).…”
mentioning
confidence: 57%
“…The spatial dependency index (SDI) corresponded to a strong spatial dependency only for the Cu attribute, classifying it as a moderate spatial dependency for the yield, C, pH, Mg, and K data. The attributes Fe, Mn, and Ca presented weak spatial dependency (Table 2), corroborating the results of Mondo et al (2012) andNegreiros Neto et al (2014). The data were interpolated by the ISD, ID, and ordinary kriging methods, and thematic maps were constructed (Figure 2).…”
mentioning
confidence: 57%
“…Segundo Lemos Filho et al (2017) a normalidade dos dados é uma condição desejável para o ajuste dos semivariogramas pela metodologia da máxima verossimilhança, devido ao fato de o ajuste do modelo de semivariograma por essa metodologia não se basear nos pontos do semivariograma, mas sim, nas diferenças dos dados originais. Porém, neste estudo, os valores de mediana e média estão próximos, destacado pelo coeficiente de curtose que deve ser preferencialmente nulo, contudo é aceito valores entre -2 e +2 (NEGREIROS NETO et al, 2014).…”
Section: Resultsunclassified
“…O restante dos atributos químicos utilizando o método de espectrofotometria de absorção atômica (ALKEMADE; MILATZ, 1955;WALSH, 1953). As análises comporam seis teses (CÁRDEÑAS, 2007;JUMBO, 2007;MORENO, 2007;PINEDA, 2007;SEDAMANOS, 2007e UZHO, 2007.…”
Section: Methodsunclassified
“…The soil, classified as Latossolo Vermelho distrófico (Santos et al, 2014) equivalent to the Rhodic Hapludox of the USDA soil classification (Soil Survey Staff, 2010), contains 680 g kg -1 clay and has been under no-tillage and conventional tillage since 1981. The conventional tillage system consists of soil preparation with the plow (Ø 0.60 m) after the harvest of the summer crop and another preparation to the depth of 0.20 m after the harvest of the winter crop, followed by two harrowings (Ø 0.40 m).…”
Section: Methodsmentioning
confidence: 99%
“…Geostatistics focuses on the spatial variability of soil nutrient levels in specific areas represented by isoline maps. Models of spatial distributions have shown that the range varies among soil attributes (DALCHIAVON et al, 2012;ARTUR et al, 2014) and tillage systems (VIEIRA et al, 2011;NEGREIROS NETO et al, 2014). Such models help optimize fertilization without harming the environment and the natural resources on which they originate.…”
Section: Introductionmentioning
confidence: 99%